Physiological time course adjustments to endurance training at altitude and tapering at sea level
A group of swimmers who trained for three weeks at altitude and another that stayed at sea level were compared. The altitude group returned to sea level for a three-week taper period and then competed in important meets. There were no differences in the performances or economy profiles of either group after the taper. This implies that there is no dvantage to training at altitude over training at sea level for the length of time of this study. It was suggested that altitude training might prove beneficial if it was done for an extended period, such as six months. The endurance capacities of the groups remained relatively unchanged over the study period. However, the anaerobic capacity of the altitude group increased markedly. During the first two weeks of adaptation, a greater anaerobic activation occurred at all swimming speeds. The length of time of increased anaerobic work was at least 12 days. It was not until the 16th day that normal training could be resumed. Implications: Short periods of altitude training produce no benefit for sea level performance. Endurance training for three weeks at altitude produces no advantage over sea level training. Sprint training may benefit from altitude training because of the increased anaerobic stimulation. Sea level re-exposure requires 16 days for a swimmer's physiology to readapt. Simply put, this study showed: Brief training periods at altitude produce no lasting effects that can benefit sea level performance; brief altitude training camps are useless; and monies for altitude camps can be better used.